2021
DOI: 10.1007/s13555-021-00658-x
|View full text |Cite
|
Sign up to set email alerts
|

Quality-of-Life Outcomes, Effectiveness and Tolerability of Apremilast in Patients with Plaque Psoriasis and Routine German Dermatology Care: Results from LAPIS-PSO

Abstract: Introduction: Psoriasis is a systemic inflammatory disease characterised by pruritic skin lesions that impair quality of life (QOL). Long-Term Documentation of the Utilization of Apremilast in Patients with Plaque Psoriasis under Routine Conditions (LAPIS-PSO; Clini-calTrials.gov: NCT02626793) was a 52-week, prospective, multicentre, observational cohort study conducted in real-world dermatology clinical settings in Germany. We evaluated physician-and patient-reported outcomes for QOL, effectiveness and tolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 30 publications
1
15
0
3
Order By: Relevance
“…The main reason for apremilast withdrawal was lack of adequate efficacy (58.5%), followed by adverse effects. Other studies also agree finding efficacy the first reason to discontinue 5,8,9,13,15 . In two of our patients apremilast was discontinued after good symptomatic control was achieved and maintained.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The main reason for apremilast withdrawal was lack of adequate efficacy (58.5%), followed by adverse effects. Other studies also agree finding efficacy the first reason to discontinue 5,8,9,13,15 . In two of our patients apremilast was discontinued after good symptomatic control was achieved and maintained.…”
Section: Discussionsupporting
confidence: 85%
“…Other studies also agree finding efficacy the first reason to discontinue. 5,8,9,13,15 In two of our patients apremilast was discontinued after good symptomatic control was achieved and maintained. Other studies also describe symptom relief as the reason to discontinue treatment in a small percentage of patients (5.4%).…”
Section: T a B L E 1 Patient Baseline Demographics And Clinical Chara...mentioning
confidence: 88%
“…2020 [ 23 ] Retrospective cohort None 85 (mean baseline PPPGA 4.2) 36.1 and 83.3 (weeks 12 and 52) (as observed) Drug survival after 1 year of treatment (%): 54.9 (includes non-palmoplantar psoriasis) Reich et al . 2019 [ 26 ] LAPIS-PSO Prospective cohort None 67 (28 with baseline PPPGA ≥ 3) PPPGA 0 or 1 (baseline PPPGA ≥ 1) (%): 62.7 and 71.7 (week 16 and 52) (full analysis set) Pavia et al . 2022 [ 24 ] Retrospective cohort None 12 (11 with baseline PPPGA ≥ 3) 90.9 (week 24) Ständer et al .…”
Section: Resultsmentioning
confidence: 99%
“…In a 52-week retrospective cohort study by the Spanish Psoriasis Group [ 23 ], the rates of patients treated with apremilast ( n = 85, mean baseline PPPGA 4.2) achieving PPPGA 0 or 1 was 36.1 and 83.3% (as observed) at weeks 12 and 52, respectively. LAPIS-PSO, a 52-week, multicenter, observational cohort study in Germany investigating apremilast treatment for PP [ 26 ], resulted in 62.7 and 71.7% of patients ( n = 67) achieving PPPGA 0 or 1 at weeks 16 and 52, respectively. A single-center retrospective cohort study by Pavia et al [ 24 ] showed 90.9% ( n = 12) of subjects with moderate to severe PP (baseline PPPGA ≥ 3) achieving clearance (PPPGA 0 or 1) after 24 weeks of apremilast treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation